Legal Consequences And Responsibilities Of Substitute Notaries For Copies Of Deeds That Differ From The Minutes Of The Deeds - Mega Junia Erliyandi; Siti Hajati Hoesin (Faculty of Law, Universitas Pekalongan, 2025)
The substitute Notary, as a public official authorized to create authentic deeds, must exercise caution and be meticulous in performing their duties when replacing a notary who is on leave, ill, or temporarily unable to perform their notarial duties. Article 65 of the Notary Position Law (UUJN) states that a Substitute Notary is also responsible for every deed they create. In practice, there is a possibility that a Substitute Notary may issue a deed copy that does not match the original deed's minute. This paper aims to examine the legal consequences and sanctions that may be imposed on a Substitute Notary in relation to discrepancies between the deed copy and the original deed minute. This study uses doctrinal research with an explanatory-analytical typology, utilizing secondary data and employing qualitative data analysis methods to present findings derived from secondary data. The conclusion indicates that discrepancies between a deed copy and the original deed minute by a Substitute Notary are not permissible in notarial practice. The Substitute Notary may be held accountable for their actions if they are proven to have made such discrepancies. The legal consequence of a deed copy differing from the original minute is that the deed is considered legally defective and is treated as a private deed. The creation of a deed copy that does not match the original minute may also cause harm to the parties involved, and sanctions can be imposed for violating the code of ethics and applicable laws and regulations. It is recommended that there be stricter supervision and continuous training for Notaries and Substitute Notaries to ensure a deep understanding of the procedures for creating authentic deeds, as well as enhanced awareness of ethics and the responsibilities of Substitute Notaries.